Pilot study of the psychological factors in the professional health of managers. - Shingaev S.M. (Psychology in Russia: State of Art, 2015)
The main research problems and tasks of a new scientific field in Russia—the psychology of professional health — are formulated. A definition of professional health as the abilities of a person successfully to cope with the demands and requirements in a professional environment is offered. A psychological vision for professional health with four basic provisions is proposed. The aim of the research was to study the extent of the influence on the professional health of managers of such psychological factors as systems of values, stress in professional activity, individual and psychological features, strategies for overcoming stressful situations. Data are provided from research conducted in 2002-2012 on managers in Russian companies. Taking part in the research were 651 managers of various organizations in St. Petersburg, Moscow, Yekaterinburg, Veliky Novgorod, and Kharkov. For collecting empirical material on methods of supervision, I used polls, tests, interviews, content analysis, self-reports of participants in training programs, and a method for forming the experiment. In addition I employed psychodiagnostic techniques intended for studying the cognitive, behavioral, and emotional components of health, a technique for revealing the personal potentials (regulatory, communicative, intellectual) of the managers, and also my own techniques. The study positively correlated health with such values as having interesting work, having a happy family life, being financially secure, having an active life, and giving and receiving love. Connections between the behavioral manifestations of type A behavior and the managers’ values were revealed. The greatest negative impact on the managers was made by such factors of professional activity as an excessive workload, emotional pressure at work, difficulty in carrying out activity, and insufficient time. Health is important in the structure of the professional activity of managers; it acts as a strategic resource by providing at the least cost efficiency and reliability during all stages of a professional career.